2015 the International Symposium on Artificial Intelligence and Signal Processing (AISP) 2015
DOI: 10.1109/aisp.2015.7123483
|View full text |Cite
|
Sign up to set email alerts
|

Link prediction in social networks using Bayesian networks

Abstract: Link prediction is as an effective technique in social network analysis to find out the relations between users and has received great concentration by many researchers in recent studies. In this paper a method is proposed for friend recommendation in social networks using Bayesian networks. The Bayesian network is a reliable model to understand the relations between variables and has been used in many areas for prediction. This method with considering effective features on creating friendships, suggests frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Das and Das [24] considered the impacts of finegrained and coarse-grained time on links, and established a Markov prediction model based on time-varying graphs of social networks, which can better predict the connection of the node pairs in a dynamic network. Shalforoushan and Jalali [25] use a bayesian network to learn the relationships between variables, and propose friend recommendation method based on Bayesian network for a social network.…”
Section: B Probabilistic Model-based Prediction Methodsmentioning
confidence: 99%
“…Das and Das [24] considered the impacts of finegrained and coarse-grained time on links, and established a Markov prediction model based on time-varying graphs of social networks, which can better predict the connection of the node pairs in a dynamic network. Shalforoushan and Jalali [25] use a bayesian network to learn the relationships between variables, and propose friend recommendation method based on Bayesian network for a social network.…”
Section: B Probabilistic Model-based Prediction Methodsmentioning
confidence: 99%
“…In [7], Papadimi-triou et al found the FriendLink Algorithm for fast and accurate link prediction in OSNs which outperforms many other related algorithms in terms of accuracy and time-complexity. Bayesian network has been also considered as a consistent model to understand the relations between future links to be predicted in networks [19], [20]. Recently, negative link prediction in social networks has attracted the attention of many researchers and considerable research work is being carried out to find efficient techniques for the same [15], [16], [18].…”
Section: Introductionmentioning
confidence: 99%